TiMER - Schaeffer, Jac; Charalambous, Harris; Caulfield, Emma; Amedori, John Patrick; Harrington, Desmond (Opening, 2011)
The premise of TiMER epitomises so much of our can't-wait-won't-wait/I-want-a-guarantee culture that it's amazing that no one has thought of it before. Sick of searching for Mr. Right? Fed up of wasting money romancing Little Miss Wrong? Then the TiMER is for you – a wrist-implanted gizmo that counts down to the exact moment when you will meet "The One". Just in case you're in any doubt, it sounds a delicate, tuneful alarm at midnight on the day they are going to turn up and, again, once your eyes meet. The catch? They have to have a TiMER too … because until your dream date gets one fitted – for $79.99 and a monthly fee of $1.99 – your wrist doohickey is destined to remain stubbornly blank. That's a problem for Oona. She's turned looking for love into a blood sport, dragging each implant-free male she falls for down to the nearest clinic to get him "tested" by TiMER. But despite being a repeat customer she has yet to find her Prince Charming. Arguably, her half-sister and best pal Steph has got even more of a problem – her TiMER reveals she's not going to meet her real deal until she's 43. Meanwhile, their little bro looks as though he's going to have no time to debate his destiny. [www.eyeforfilm.co.uk]